PENGEMBANGAN VIDEO PEMBELAJARAN ANIMASI CANVA BELAJAR MESIR (MENELADANI 4 SIFAT RASUL) PADA PEMBELAJARAN PAI KELAS 2 SD - Lestari, Loro; Musyarofah, Aida; Sunasi, Fera Tri; Aeni, Ani Nur (Universitas Negeri Medan, 2024)
Abstract : Knowing the 4 Attributes of the Prophet Muhammad in the learning process is something that is quite important to teach from an early age. These qualities serve as moral and spiritual guidance for Muslims in living their daily lives. This research was carried out with the aim of developing learning videos related to Ethics/Morals/Akhlak in an Islamic Perspective. This learning video contains stories of people who apply and do not apply the 4 characteristics of the Prophet Muhammad SAW. As an effort to motivate students in PAI subjects in the material on the 4 characteristics of the Prophet Muhammad SAW, so as to create a fun and interactive learning atmosphere. The research method used was the Design and Development (D&D) method. This research has a population of 20 2nd grade elementary school students. This elementary school is located in Karanglayung, Conggeang District, Sumedang Regency. . The results of this research show that the use of learning videos regarding the 4 characteristics of the Prophet Muhammad SAW as a learning medium for students in elementary school is expected to be a stimulus and basic education for students to learn to be responsible, honest and trustworthy. Keyword : 4 characteristics of the Prophet Abstrak : Mengetahui 4 Sifat Nabi Muhammad dalam proses pembelajaran menjadi hal yang cukup penting diajarkan sejak dini. Sifat-sifat ini menjadi panduan moral dan spiritual bagi umat Islam dalam menjalani kehidupan mereka sehari-hari. Penelitian ini dilakukan bertujuan untuk mengembangkan video pembelajaran berkaitan dengan Etika/ Moral/ Akhlak Dalam Perspektif Islam. Video pembelajaran ini berisi tentang kisah orang yang menerapkan dan tidak menerapkan 4 sifat Nabi Muhammad SAW Sebagai upaya untuk memotivasi siswa pada mata pelajaran PAI dalam materi 4 sifat Nabi Muhammad SAW, sehingga terciptanya suasana pembelajaran yang menyenangkan dan interaktif. Metode penelitian yang dilakukan adalah metode Design and Development (D&D). Penelitian ini memiliki populasi yaitu siswa kelas 2 SD sebanyak 20 orang, SD ini terletak di Karanglayung Kecamatan Conggeang Kabupaten Sumedang. Hasil penelitian ini menunjukan bahwa, pemanfaatan video pembelajaran mengenai 4 sifat Nabi Muhammad SAW Sebagai Media Pembelajaran Siswa Di SD diharapkan dapat menjadi stimulus dan pendidikan dasar bagi peserta didik untuk belajar bertanggung jawab, jujur dan Amanah. Kata kunci: video pembelajaran 4 sifat rasul.